Long term survival and prognostic factors for Thymoma and Thymic carcinoma. Results from a tertiary care center - Thakur, Binay; Zhenqing, Sun; Khatiwada, Sagar; Tiwari, Manoj; Bhattarai, Shachee; Shrestha, Shashank; Kharel, Ashish; Adhikari , Mahesh Mani; Thapa, Asha (Nepalese Journal of Cancer, 2024)
Background: Thymomas and thymic carcinoma are rare tumors though thymoma is the most common anterior mediastinal neoplasm. We aimed to determine the long-term survival after thymectomy and also to identify the poor prognostic factors of survival. Methods: A retrospective analysis of tumors with the final diagnosis of thymoma or thymic carcinoma (n = 42) was done. Upfront surgery or a multimodality approach was used depending upon Masaoka-Koga stage. Statistical analysis was done using SPSS 26.0 Results: Median survival was 144, 97, 123, 45, 19 and 20 months in Masaoka-Koga stages 1, 2a, 2b, 3, 4a and 4b, respectively (p < 0.001). Median survival and five-year overall survival (OS) were 86 months and 60%, respectively. Median OS was 125, 25 and 24 months for R0, R1 and R2 resections, respectively (p < 0.001). Median OS was 123 months in no-tumor spillage group vs 24 months in tumor spillage group (p < 0.001). Conclusion: Masaoka-Koga stage, resection status and intraoperative tumor spillage are the most important predictors of long-term survival.